Comparative Study of Pitting Corrosion in 316L Stainless Steel Using Different Metal Additive Manufacturing Techniques - Leow, Tze Yi; Liew, Kia Wai; Canturri, Carla; Ng, Poh Kiat; ., Aishwarya; Shandro, Robert (International Journal of Membrane Science and Technology, 2023)
316L stainless steel is a commonly used material in a range of industries, including the automotive and aerospace industries, due to its advantageous mechanical properties, such as high yield strength and outstanding corrosion resistance. In recent years, the use of metal additive manufacturing technologies for fabricating 316L stainless steel has become more common, as it permits the creation of intricate geometries that are difficult to achieve through conventional manufacturing techniques. Nevertheless, certain characteristics of additive-manufactured 316L stainless steel, such as its pitting corrosion resistance, remain insufficiently understood. In the present experimental study, a pitting corrosion test was performed in accordance with ASTM G48 standards. The pitting corrosion test was conducted with the use of ferric chloride solution on 316L LPBF, 316L MBJ, and 316L WAAM additive-manufactured stainless steel. The data was compared to wrought 316L stainless steel. The results of the investigation indicate that 316L LPBF exhibited the highest pitting corrosion resistance, followed by 316L WAAM, wrought 316L, and 316L MBJ. Microstructure analysis further demonstrated that grain size played significant roles in the pitting corrosion resistance performance of the materials, with smaller grain size yielding superior performance. Additionally, Vickers hardness testing revealed that specimens with higher hardness exhibited better pitting corrosion resistance.